Numerical simulation and experimental study of bypass pigging slippage. (15th June 2021) - Li, Xiaowei; He, Limin; Luo, Xiaoming; Liu, Haixiao; He, Songtao; Li, Qingping
Abstract: In traditional pigging operations, sealed disks having a specific amount of interference guarantee that the pig runs at the velocity of the gas behind it. A bypass flow path in the pig lowers its speed while causes the uneven pig motion, which is referred to as slippage. The slippage raises the risk of the pig becoming stuck and negatively impacts the pipe and related facilities. This paper proposes a numerical method to solve a pigging model consisting of arbitrary Lagrange-Euler forms of the fluid flow equations and the bypass pig kinetic equation based on the moving grid method, which considers the contact surfaces between the pig and the fluid as discretized grid nodes. A detailed moving mesh was adopted to study the flow field around the pig. The consistency between the numerical and experimental results demonstrates the accuracy and applicability of the numerical method. Gas compressibility is primarily responsible for the transitional motions of the pig, especially its gradual restarting and the gradually smoothed velocity. Furthermore, the variation in the friction force is the primary factor that determines the appearance of the pigging stoppage and the scale of the pig resting and the next uneven pig velocity. Highlights: A novel moving grid pigging simulation is proposed. Gas compressibility is responsible for the pig starting stoppage. Friction determines the scales of the unsteady pig motion.